A Comparative Study of Minimal Invasive and Open Colorectal Surgeries with Regards To PostOperative Hospital Stay and Complications - Farooq, Muhammad Zain; Mahmood, Khalid; Zafar, Muhammad Arsalan; Chatha, Sohail Saqib; Saeed, Muhammad Farhan; Qureshi, Tansheet Mazhar (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To compare outcomes of laparoscopic surgery versus open surgery for colorectal carcinoma in terms of hospital stay and post-operative complications. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi, from Mar 2020 to Mar 2021. Methodology: We studied a total of 114 patients who were diagnosed with colorectal cancer and met the sample selection criteria. Patients with metastatic disease or previous history of abdominal surgery were excluded from the study. Patients were documented for hospital stay and followed for six months for the development of complications. Data was analyzed by SPSS version 26. Results: We studied a population where 45 (39.5%) were male while 69 (60.5%) were female. The mean age of the sample was 46.96 ± 14.47 years. The study showed that the mean hospital stay was shorter in Group A: 5.40 ± 1.88 days versus 6.59 ± 1.68 days in Group B (p=0.001). Mean blood loss was 65.99 ± 16.41 mL in Group A versus 366.93 ± 95.36 in Group B (p<0.001). The complication rates in Group A and B were 6 (10.5%) and 11 (19.2%), respectively (p=0.18), while the rate of incisional hernia formation was 0 (0%) and 4 (6.9%) (p=0.042). Conclusion: Laparoscopic surgery is superior to open surgery is the management in terms of shorter in-hospital stay and postoperative complications.